RANCANGAN ALUR PENDAFTARAN PASIEN RAWAT INAP DARI POLIKLINIK MENGGUNAKAN MEDIA AKRILIK DINDING DI RSUD KABUPATEN JOMBANG - Dwi Wulandari; Dea Allan Karunia Sakti; Honggo Dewanto (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2022)
SIMRS is used in the patient registration process, one of which is the registration of the patient in the hospital. The stages of hospital patient registration are pre-admission, elective admission, and payment. The initial registration of patients in the hospital is only done through two doors: the Poliklinik and the UGD . (Unit Gawat Darurat). One of the problems with the registration of hospital patients is that (1) the absence of a hospital patient registration flow from the Poliklinik or IGD causes confusion for the patient or their family. (2) Patients and families complain about hospital registration at the polyclinic because there are frequent errors and long loadings on the SIMRS. (3) The hospital admission space is too small or closed. Methods used in research II are qualitative methods with case study approaches. The instruments used are interviews and observations. The study conducted analysis using the methods of ultrasound and fishbone to determine the priority of the problem, and the implementation of the hospital patient registration process was carried out by applying acrylic walls in the hospital admission section and conducting observations for 2 days that showed that there was a level of awareness or information given to the patient about the process and the course of hospital patient registration. Students can make a design of the patient's registration cycle from a poliklinic, and based on the results of observation over two days, it is known that there are 15–17 patients who are responsible for having observed the registry cycle of hospital patients from the poliklinic.